2024
DOI: 10.1088/1361-6501/ad197a
|View full text |Cite
|
Sign up to set email alerts
|

Attention mechanism guided sparse filtering for mechanical intelligent fault diagnosis under variable speed condition

Rui Han,
Jinrui Wang,
Yanbin Wan
et al.

Abstract: Variable speed is one of the common working conditions of mechanical equipment,which poses an important challenge to equipment fault diagnosis. The current solutions have the shortcomings of low computational efficiency and large diagnostic errors. The ability of attention mechanism to automatically extract useful features has begun to attract widespread attention in the field of mechanical intelligent fault diagnosis. Combining the advantages of attention mechanism and unsupervised learning, this paper propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Attention mechanisms have revolutionized the way neural networks process information by enabling models to focus on specific parts of the input data, improving efficiency and performance across tasks such as classification, prediction and beyond UrRehman et al (2024). In recent years, an increasing number of empirical studies have demonstrated the significant role of incorporating attention mechanisms into bearing fault diagnosis Yao et al (2023), Dong et al (2024), Han et al (2024). This approach allows the model to selectively focus on key data points, thereby enhancing its ability to identify important fault characteristics with greater accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Attention mechanisms have revolutionized the way neural networks process information by enabling models to focus on specific parts of the input data, improving efficiency and performance across tasks such as classification, prediction and beyond UrRehman et al (2024). In recent years, an increasing number of empirical studies have demonstrated the significant role of incorporating attention mechanisms into bearing fault diagnosis Yao et al (2023), Dong et al (2024), Han et al (2024). This approach allows the model to selectively focus on key data points, thereby enhancing its ability to identify important fault characteristics with greater accuracy.…”
Section: Introductionmentioning
confidence: 99%